Adaptation Challenges of Domestic and International Students in a Russian English-Medium Instruction University - Volkova, Natalia V.; Kolesov, Anatoliy A. (Journal of International Students, 2021)
With the increasing focus on the internationalization of higher education, universities are developing student mobility. This paper examines the challenges experienced by domestic and international students who adapt to a Russian English-medium instruction university. A mixed-method approach with interviews and surveys was utilized to specify, evaluate, and discuss the students’ internationalization experiences in these educational settings. The results indicated that both groups of students mentioned different aspects of language barriers, friendship networks, and university social life as critical areas for adjustment. Domestic students avoid taking part in university social life, instead focusing on their academic performance, this fact probably rooted in the Russian approach to secondary education. The specific finding of the Russian educational landscape is a lack of differences between domestic and international students concerning academic integration. These suggest institutions to adopt more student-oriented adaptation mechanisms, informed by the concept of inclusion in education; these implications are discussed.